Omitting types and w-categoricity for linear kripke sheaves (2017)
"Kripke semantics constitutes a correct and complete system for intuitionistic logic (concretely for Heyting's calculus), nevertheless there are few approaches exploring model theoretical questions in this context. Based on a new proof of completeness for Kripke models over linearly ordered sets we prove an omitting types theorem which permits some versions of Ryll Nardzewski theorem for the corresponding logic". -- Tomado del Formato de Documento de Grado.